2019
DOI: 10.1002/pbc.27701
|View full text |Cite
|
Sign up to set email alerts
|

Use of granulocyte colony‐stimulating factor and risk of relapse in pediatric patients treated for acute myeloid leukemia according to NOPHO‐AML 2004 and DB AML‐01

Abstract: Background Supportive‐care use of granulocyte colony‐stimulating factor (G‐CSF) in pediatric acute myeloid leukemia (AML) remains controversial due to a theoretical increased risk of relapse and limited impact on neutropenic complications. We describe the use of G‐CSF in patients treated according to NOPHO‐AML 2004 and DB AML‐01 and investigated associations with relapse. Procedure Patients diagnosed with de novo AML completing the first week of therapy and not treated with hematopoietic stem cell transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…G‐CSF is essential for the survival and proliferation of the granulocyte haematopoietic stem (progenitor) cells, and has been used to decrease severe infections and treatment‐related mortality in AML due to the widespread expression of its receptor (G‐CSFR) on AML cells. However, although Saito et al () found that G‐CSF increased elimination of human primary AML stem cells in vivo , other studies have suggested that G‐CSF contributes to myeloid cell growth (Zhu et al , ) and even increases the risk of relapse (Lohmann et al , ). G‐CSF secretion increased significantly in MSC‐AML cell co‐cultures (Brenner et al , ), and van den Berk et al () observed a clear upregulation of G‐CSF along with leukaemic cell expansion in the presence of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…G‐CSF is essential for the survival and proliferation of the granulocyte haematopoietic stem (progenitor) cells, and has been used to decrease severe infections and treatment‐related mortality in AML due to the widespread expression of its receptor (G‐CSFR) on AML cells. However, although Saito et al () found that G‐CSF increased elimination of human primary AML stem cells in vivo , other studies have suggested that G‐CSF contributes to myeloid cell growth (Zhu et al , ) and even increases the risk of relapse (Lohmann et al , ). G‐CSF secretion increased significantly in MSC‐AML cell co‐cultures (Brenner et al , ), and van den Berk et al () observed a clear upregulation of G‐CSF along with leukaemic cell expansion in the presence of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used prophylactic G-CSF in all patients with no adverse outcomes even though some studies have documented higher risk of relapse with G-CSF. [21,22] Our policy of use of G-CSF in children with AML post induction chemotherapy is guided by various publications in literature where G-CSF has not been associated with increased risk of relapse. [23] In a Cochrane review where 19 studies with more than 5000 patients were analyzed, relapse rates did not increase due to use of CSFs.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the same group reported that children with the isoform IV of the G-CSF receptor might have an increased risk of relapse when prophylactically treated with G-CSF [61]. A retrospective study by NOPHO-AML2004 and DB-AML-01 showed that patients who had received G-CSF during treatment, mainly due to infection, had a higher risk of relapse than those who had not received G-CSF [62].…”
Section: Use Of Granulocyte Colony-stimulating Factor (G-csf)mentioning
confidence: 99%